Identification of Key Regulators of Hepatitis C Virus-Induced Hepatocellular Carcinoma by Integrating Whole-Genome and Transcriptome Sequencing Data - Chen, Guolin; Zhang, Wei; Ben, Yiran (Frontiers in Genetics, 2021)
Background: Hepatitis C virus (HCV) infection is a major cause of cirrhosis and hepatocellular carcinoma (HCC). Despite recent advances in the understanding of the biological basis of HCC development, the molecular mechanisms underlying HCV-induced HCC (HCV–HCC) remain unclear. HCV’s carcinogenic potential varies according to the genotype and mutation in its viral sequence. Moreover, regulatory pathways play important roles in many pathogenic processes. Therefore, identifying the pathways by which HCV induces HCC may enable improved HCC diagnosis and treatment. Methods: We employed a systematic approach to identify an important regulatory module in the process of HCV–HCC development to find the important regulators. First, an HCV-related HCC subnetwork was constructed based on the gene expression in HCC–HCV patients and HCC patients. A priority algorithm was then used to extract the module from the subnetworks, and all the regulatory relationships of the core genes of the network were extracted. Integrating the significantly highly mutated genes involved in the HCC–HCV patients, core regulatory modules and key regulators related to disease prognosis and progression were identified. Result: The key regulatory genes including EXO1, VCAN, KIT, and hsa-miR-200c-5p were found to play vital roles in HCV–HCC development. Based on the statistics analysis, EXO1, VCAN, and KIT mutations are potential biomarkers for HCV–HCC prognosis at the genomic level, whereas has-miR-200c-5P is a potential biomarker for HCV–HCC prognosis at the expression level. Conclusion: We identified three significantly mutated genes and one differentially expressed miRNA, all related to HCC prognosis. As potential pathogenic factors of HCC, these genes and the miRNA could be new biomarkers for HCV–HCC diagnosis.